2001
DOI: 10.1053/ajkd.2001.29222
|View full text |Cite
|
Sign up to set email alerts
|

A Malnutrition-Inflammation Score is correlated with morbidity and mortality in maintenance hemodialysis patients

Abstract: Malnutrition inflammation complex syndrome (MICS) occurs commonly in maintenance hemodialysis (MHD) patients and may correlate with increased morbidity and mortality. An optimal, comprehensive, quantitative system that assesses MICS could be a useful measure of clinical status and may be a predictor of outcome in MHD patients. We therefore attempted to develop and validate such an instrument, comparing it with conventional measures of nutrition and inflammation, as well as prospective hospitalization and morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
724
5
53

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 840 publications
(804 citation statements)
references
References 29 publications
22
724
5
53
Order By: Relevance
“…In HD patients, MIS is strongly correlated with the measures of nutrition and inflammation as well as prospective hospitalizations and mortality (Kalantar-Zadeh et al, 2001). In our study, we demonstrated that there is an ongoing and chronic process of malnutrition and inflammation in HCV-infected HD patients with CAD.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In HD patients, MIS is strongly correlated with the measures of nutrition and inflammation as well as prospective hospitalizations and mortality (Kalantar-Zadeh et al, 2001). In our study, we demonstrated that there is an ongoing and chronic process of malnutrition and inflammation in HCV-infected HD patients with CAD.…”
Section: Discussionsupporting
confidence: 53%
“…The sum of the 10 components changes between 0 and 30. A higher score reflects a more severe degree of malnutrition and inflammation (Kalantar-Zadeh et al, 2001).…”
Section: Malnutrition Inflammation Scorementioning
confidence: 99%
See 1 more Smart Citation
“…The major negative impact of chronic inflammation on nutritional status and survival of patients on maintenance hemodialysis has been documented by many studies, 11,16 and it is clear that the presence of acute or chronic inflammation limits the specificity of serum albumin as a nutritional marker. 1 Markers of inflammation were not routinely measured in the units of the DOPPS; however, we were able to design a Malnutrition Inflammation Score (MIS) from the work of Kalantar-Zadeh et al 20 A modified MIS, ranging from 0 to 30, was devised using DOPPS I data from more than 6,000 patients from the United States, Japan, and Europe, with a higher MIS indicating a worse nutrition-inflammation status. 21 Preliminary results indicate that the average MIS ranged from 5.8 in Japan to 10.7 in Germany, with the other 5 countries ranging from 9.0 to 10.1.…”
Section: Other Variables Linked To Nutritional Statusmentioning
confidence: 99%
“…The sum of scores ranges from zero to 30 indicates a normal nutritional status or mild malnutrition; a score of 9-18 indicates moderate malnutrition, and a score greater than 18, severe malnutrition. This score provides a correlation coefficient greater than isolated laboratory values and other scores such as SGA 23,24 .…”
Section: Erythropoietin Resistance Indexmentioning
confidence: 93%